Answer:
![y=\frac12x+\frac52](https://img.qammunity.org/2023/formulas/mathematics/college/6n9ej90kreepv0o9qflplfogdmittezgk7.png)
Explanation:
M = (-1, 7)
N = (3, -1)
![\sf slope\:of\:MN=(y_n-y_m)/(x_n-x_m)= (-1-7)/(3-(-1))=-2](https://img.qammunity.org/2023/formulas/mathematics/college/kktp9rdpsg6gqncyn5zorhg9qk56y6d787.png)
If two lines are perpendicular to each other, the product of their slopes will be -1. Therefore, the slope (m) of the line perpendicular to MN is:
![\sf \implies -2 * m=-1](https://img.qammunity.org/2023/formulas/mathematics/college/stdhtby7cuhyf2rxnzs7u66bdxdn83389q.png)
![\sf \implies m=\frac12](https://img.qammunity.org/2023/formulas/mathematics/college/cjtegyj0xf0dg4cse6nllwhjywhct6fiaz.png)
If the line bisects the line MN, it will intersect it at the midpoint of MN:
![\begin{aligned}\textsf{Midpoint of MN} & =\left((x_m+x_n)/(2),(y_m+y_n)/(2)\right)\\ & =\left((-1+3)/(2),(7+(-1))/(2)\right)\\ & =(1,3)\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/ho2uywy5yuy5fapefd86e6cjhrp2c3r48m.png)
Finally, use the point-slope form of the linear equation with the found slope and the midpoint of MN:
![y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csobd57zth7rh9k4hz9amldzpq2owf0z4j.png)
![\implies y-3=\frac12(x-1)](https://img.qammunity.org/2023/formulas/mathematics/college/epd7hcsbav4mcl8vvxykufw7ssyw30ny60.png)